Quantification of torque teno virus load to monitor short-term changes in immunosuppressive therapy in kidney transplant recipients - Benning, Louise; Reineke, Marvin; Bundschuh, Christian; Klein, Julian; Kühn, Tessa; Zeier, Martin; Bartenschlager, Ralf; Schnitzler, Paul; Morath, Christian; Speer, Claudius (Transplantation, 2023)
Background. - Quantification of torque teno virus (TTV) has been proposed as a surrogate parameter to monitor immunocompetence in kidney transplant recipients (KTRs) early after transplantation. However, its use in monitoring short-term changes of immunosuppression in KTRs late after transplantation requires further investigation. - Methods. - In this post hoc analysis, we quantified TTV load in sera of 76 KTRs, with 43 pausing mycophenolic acid (MPA) 1 wk before to 4 wk after COVID-19 vaccination to increase vaccine response. TTV load was quantified before, 4 wk, and 3 mo postvaccination. Results were compared to 33 KTRs with continued standard immunosuppressive therapy and with 18 hemodialysis as well as 18 healthy control subjects. - Results. - TTV load before vaccination was with a median (interquartile range) of 1.39 × 104 copies/milliliter (c/mL) (9.17 × 101-2.66 × 105 c/mL) highest in KTRs compared to 1.73 × 103 c/mL (1.07 × 103-1.31 × 104 c/mL) in hemodialysis patients and 1.53 × 102 c/mL (6.38-1.29 × 103 c/mL) in healthy controls. In KTRs with MPA withdrawal, TTV load decreased significantly from a median (interquartile range) of 1.11 × 104 c/mL (4.75 × 102-1.92 × 105 c/mL) to 5.24 × 103 c/mL (6.92 × 102-6.91 × 104 c/mL) 4-5 wk after initiation of MPA withdrawal (P = 0.003). In patients with MPA withdrawal, TTV load was significantly inversely correlated with COVID-19 or SARS-CoV-2-specific antibodies 4 wk and 3 mo postvaccination (P = 0.009 and P = 0.004). - Conclusions. - TTV load reflects changes in immunosuppressive therapy even late after transplantation, supporting its use to monitor immunocompetence in KTRs. - - - - - Export
Gesehen am 26.01.2024